Efecto de recubrimientos comestibles formulados a base de alginato, carboximetilcelulosa y proteína de suero de leche en la vida útil de la remolacha (Beta vulgaris L.) mínimamente procesada. - Armijos Piedra, María Alejandra. (2015)
The objective of this study was determine the effect of disinfectants in the development and preparation of beet MMP and to evaluate the effect of RC-based alginate, carboxymethylcellulose and protein on the quality of beet MMP. Beets were disinfected with chlorine, ozone and UV-C, quality parameters like color, liquid release, weight loss and microbiological. Ozone was the one that stood out as the best disinfectant, as it allowed reducing microbial counts and maintain good visual quality. Alginate coatings subsequently 0.5%, 0.5% CMC and protein 10% were applied to determine the effect on the aforementioned parameters. CMC coating further remained in color. Also had higher sensory acceptance, since the end of storage beets coated with CMC were rated as "good" and the uncoated as "very unpleasant", so the RC are an alternative for the conservation of beet MMP.